2018
DOI: 10.1002/chem.201802384
|View full text |Cite
|
Sign up to set email alerts
|

Radical‐Triggered Three‐Component Coupling Reaction of Alkenylboronates, α‐Halocarbonyl Compounds, and Organolithium Reagents: The Inverse Ylid Mechanism

Abstract: An operationally simple protocol to affect a radical addition to alkenylboronates that spontaneously undergo a [1,2]-metalate shift is described. Overall, the reaction is a three-component coupling of an organolithium, alkenylboronic ester, and halide which takes place with broad scope and good to excellent yields. Experimental mechanistic investigations support the formation of a boron inverse ylid intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 36 publications
0
53
2
Order By: Relevance
“…[121] Denmark et al have recentlyp ublished ar eport on the transition-metal-free enantioselective carbosulfenylation of alkenyl boronates to afford b-sulfur secondaryo rt ertiary alcohols after oxidation (Scheme 28c). [122] The aforementioned substrates, tetracoordinated alkenyl boronate complexes, have also been employed in radical chemistry.S tuder et al [123] and Aggarwal et al, [124] independently,a nd later Renaud and co-workers, [125] have shown that the vinyl boronate complexes are efficient radical acceptors, and the radicala nion adducts undergo 1,2-alkyl/aryl shifts from boron to carbon,t hus leading to av ariety of synthetically useful products (Scheme 29a). This method has been applied by Aggarwal's group with heterocycles such as furan or indole to give 2,5-disubstituted furanso r2 ,3-disubstituted indoles (Scheme29b).…”
Section: Applications Of Alkenyl Boronatesmentioning
confidence: 99%
See 1 more Smart Citation
“…[121] Denmark et al have recentlyp ublished ar eport on the transition-metal-free enantioselective carbosulfenylation of alkenyl boronates to afford b-sulfur secondaryo rt ertiary alcohols after oxidation (Scheme 28c). [122] The aforementioned substrates, tetracoordinated alkenyl boronate complexes, have also been employed in radical chemistry.S tuder et al [123] and Aggarwal et al, [124] independently,a nd later Renaud and co-workers, [125] have shown that the vinyl boronate complexes are efficient radical acceptors, and the radicala nion adducts undergo 1,2-alkyl/aryl shifts from boron to carbon,t hus leading to av ariety of synthetically useful products (Scheme 29a). This method has been applied by Aggarwal's group with heterocycles such as furan or indole to give 2,5-disubstituted furanso r2 ,3-disubstituted indoles (Scheme29b).…”
Section: Applications Of Alkenyl Boronatesmentioning
confidence: 99%
“…[123b,c] Simple vinyl-BMIDA and vinyl-Bpin are also suitable substrates for radical chemistry. [125]…”
Section: Applications Of Alkenyl Boronatesmentioning
confidence: 99%
“…1‐Borylated alkyl radicals have also been generated from Barton esters and xanthates as well as through radical addition to vinylboronates . and to ate complexes of vinylboronates . To the best of our knowledge, no halogen atom‐transfer radical addition (ATRA) process involving 1‐haloalkylboronates has been reported.…”
Section: Figurementioning
confidence: 99%
“…[53] Interestingly,p inacol iodomethylboronic Figure 1. [62][63][64] To the best of our knowledge,n oh alogen atom-transfer radical addition (ATRA) process involving 1-haloalkylboronates has been reported. [34] Scheme 1.…”
mentioning
confidence: 99%
“…[43,44,46,[57][58][59][60][61] and to ate complexes of vinylboronates. [62][63][64] To the best of our knowledge,n oh alogen atom-transfer radical addition (ATRA) process involving 1-haloalkylboronates has been reported. This reaction would be highly attractive since it would open aw ay for the straightforward preparation of 3-haloalkylboronates that are potential precursors of cyclopropanes through a1 ,3-elimination process.…”
mentioning
confidence: 99%